Uncommon paths in quantum physics - Kazakov, Konstantin V. (Amsterdam : Elsevier, 2014)
Quantum mechanics is one of the most fascinating, and at the same time most controversial, branches of contemporary science. Disputes have accompanied this science since its birth and have not ceased to this day. Uncommon Paths in Quantum Physics allows the reader to contemplate deeply some ideas and methods that are seldom met in the contemporary literature. Instead of widespread recipes of mathematical physics, based on the solutions of integro-differential equations, the book follows logical and partly intuitional derivations of non-commutative algebra. Readers can directly penetrate the abstract world of quantum mechanics.
Regularization of interaction energy5 Radiative corrections; Renormalization of mass; Anomalous magnetic moment of the electron; On the history of radiative corrections; Bethe's formula; Electromagnetic shift of atomic levels; Vacuum polarization; Renormalization of charge; Dirac's ideas and quantum field theory; Bibliography.
Print version record.
Keywords: Quantum theory -- Mathematics; Noncommutative algebras; SCIENCE -- Energy; SCIENCE -- Mechanics -- General; SCIENCE -- Physics -- General; Noncommutative algebras; Quantum theory -- Mathematics; Electronic books